Pengambilan Keputusan Mahasiswa Lulusan Pendidikan Agama Islam Universitas Negeri Padang dalam Memilih Bekerja di Bidang Non-Kependidikan - Marsha Hasya; Rengga Satria (FONDATIA, 2022)
Judging from the realm of Islamic Religious Education graduates, they have a graduate profile that is expected to be a center in education that produces superior Islamic Educators. However, in reality, there are students who graduate from Islamic Religious Education who have a background as educators or education graduates who prefer to work in non-educational fields. The impact of this phenomenon itself can lead to other phenomena, so this study seeks to provide a description of how this phenomenon can occur and of course this is influenced by several factors in decision making, decision-making styles and what difficulties are faced after making a decision to work in a non-profit sector. education. This study uses a qualitative method with a descriptive approach. Sources of data came from 10 students who graduated from Islamic Religious Education UNP who worked in the non-educational field by conducting in-depth interviews. The results of the interviews were analyzed systematically with four stages, namely data collection, data reduction, data presentation and conclusion drawing. Overall, the results of the analysis show that the internal factors that influence the decision making of PAI graduate students are interests and talents, as well as personality. Then three external factors that influence, namely: 1) parents, 2) environment, 3) salary/financial. Meanwhile, there are two decision-making styles used by PAI graduate students, namely the rational style and the intuitive style.